Ticks (Argasidae, Ixodidae) and tick-borne diseases of continental Southeast Asia - Petney, Trevor N; Saijuntha, Weerachai; Boulanger, Nathalie; Chitimia-Dobler, Lidia; Pfeffer, Martin; Eamudomkarn, Chatanun; Andrews, Ross H; Ahamad, Mariana; Putthasorn, Noppadon; Muders, Senta V; Petney, David A; Robbins, Richard G (Zootaxa, 2019)
Knowledge of the tick fauna of continental Southeast Asia is either patchy or, in some cases, for example Cambodia and Myanmar, poor. Nevertheless, 97 species have been recorded from this region, making it one of the most diverse for ticks worldwide. Throughout Southeast Asia, work on tick-borne diseases of stock and companion animals, as well as of humans, is in its infancy, and the medical, veterinary and socio-economic importance of these diseases is largely unknown. Here we review current knowledge of Southeast Asian ticks and tick-borne diseases, with the aim of stimulating further research on this subject.